THE C.P.A. REVIEW COURSE. - Winter, S. G. (The Accounting Review, 1935)
Abstract A C.P.A.-review course seems to be regarded generally as designed to meet certain needs of a relatively small group of students. It usually appeals to those who are interested primarily in professional accounting work and who hope to receive the certificate of certified public accountant, that magic parchment which, in the eyes of the layman, approximates a guaranteed income of anything above ten thousand dollars per annum to the holder thereof. One should include among these "professional students" the few who are interested in the executive accounting positions of certain of the larger corporations, the positions of auditor, comptroller, cost accountant, or budget officer. Students enrolling in the C.P.A.-review course must have a minimum of fifteen hours in prerequisite courses, elementary accounting, intermediate accounting, and cost accounting. It is customary for the student to have, in addition to the foregoing, credit in accounting systems, one semester of the year course in auditing, advanced accounting, and a second course in cost accounting. The basic textbook selected should provide answers and solutions in loose-leaf form.